Replication Data for: Smallholder farmers’ attitudes and determinants of adaptation to climate risks in East Africa - Shikuku, Kelvin Mashisia; Winowiecki, Leigh Ann; Twyman, Jennifer; Eitzinger, Anton; Pérez, Juan G.; Mwongera, Caroline; Läderach, Peter R.D. (International Center for Tropical Agriculture, 2017)
The objective of organizing this dataset was to measure farmers’ attitudes and assess determinants of adaptation to climate risks in East Africa. This dataset comprises information about farmers’ adaptation strategies to climate risks in four CCAFS sites in east Africa, namely Nyando, Kenya; Hoima, Uganda; Lushoto, Tanzania; and Borana, Ethiopia. Data were collected via personal interviews by trained enumerators using pre-designed and pre-tested questionnaires. The variables contained in the dataset come from a baseline survey that was conducted by the CGIAR program on Climate Change, Agriculture, and Food Security (CCAFS) in 2010 and a follow up survey by the International Center for Tropical Agriculture (CIAT) in 2012. The variables include farmer and household characteristics such as age, education, sex, household size; adaptation strategies, and assets index. The total sample size is 500 farming households.